Sensibility of sugarcane cultivars to pre and post-emergence herbicides - Castro, Fernanda Maria Rodrigues; Bruzi, Adriano Teodoro; Mourão, Marcos Machado; Andrade, Luiz Antônio de Bastos; Gonçalves, Adenilson Henrique; Nunes, José Airton Rodrigues (Revista Agrogeoambiental, 2019)
Chemical control is used to restrain the attack of weeds on cultivated crops in Brazil; however, the overuse of chemical products can cause damage to the crops. This study aimed to evaluate the phytotoxicity caused by pre-emergence (PRE) and post-emergence (POST) herbicides in sugarcane cultivars and their influence in agronomic and technological traits as well as to verify the existence of correlation between the herbicides effect and the measured traits. The experiment was carried out in a randomized complete block design with three replications, considering the factorial combination of five sugarcane cultivars and five control strategies, being four herbicides and one control. The sensitivity was evaluated at 30, 60 and 90 days after application, through a scale of intoxication symptoms. The herbicides with active ingredients diuron + hexazinone and ametryn presented more phytotoxicity effect; the cultivars RB867515 and SP81-3250 showed greater toxicity symptoms when exposed to the agrochemicals. Plant height was the only trait influenced by the herbicides. It was observed a significant correlation between the trait number of stems and phytotoxicity effect.